Video games reviewed as framing tool for political actor in petualangan Jokowi games - Wahyu Juliangga (Jurnal Kajian Komunikasi, 2021)
Digitalization created new development in the interactive model used by political actors. One of the models is video games as a propaganda tool for electoral interest. This study tries to elaborate on the role of a video game called “Petualangan Jokowi.” This study used Political Campaigning Games (PCG) framework with game analysis as the primary method with textual and user experience approach by the casual gamers. This study showed that the video game “Petualangan Jokowi” on advergames definition based on textual approach is a by-design game for promoting Joko Widodo and another political actor inside the games to casual gamers. This game succeeds in partially framing the political actors’ characters who will be the focus inside Petualangan Jokowi. But the casual gamers are distressed to get the political message which is shown by the symbol and the story because of the shortcoming of development in content and functionality. This study also indicates casual gamers do not want to stick outplayed Petualangan Jokowi because there is no incentive for casual gamers to play Petualangan Jokowi for a long time. This factor implies the not effectively framing process because the casual gamers only received partial political messages based on lack of experience played Petualangan Jokowi.